Prevention of Diabetes Mellitus Through Physical Exercise in the Cihanjuang Village Community - Handariati, Atik; Salihun, Saleha; Maulida, Gina Rizkyani; Putra Mardiansyah, Muhammad Faizal (Rifa'Institute, 2025)
Introduction: Diabetes mellitus has become a growing public health concern in Indonesia, and rural communities are increasingly exposed to lifestyle-related risk factors while maintaining traditional work patterns. Objective: This study aimed to explore how community members in Desa Cihanjuang understand and practise physical activity as a strategy for preventing diabetes mellitus. Method: A qualitative descriptive design within an interpretivist–constructivist paradigm was employed. Twenty-two participants, including adult residents, community health cadres, health workers, and village leaders, were selected through purposive sampling. Data were generated through semi-structured interviews, focus group discussions, non-participant observation, and document review, and were analysed using reflexive thematic analysis. Result and Discussion: The analysis yielded four main themes: physical activity is largely perceived as ordinary work rather than intentional exercise; awareness of diabetes risk and the preventive role of physical activity is emerging but uneven; social, cultural, and environmental constraints limit engagement in structured exercise; and community-driven strategies, particularly group-based activities integrated into existing health programmes, represent promising entry points. Conclusions: Diabetes mellitus prevention in Desa Cihanjuang requires context-sensitive interventions that reframe physical activity, address everyday constraints, and strengthen community-led initiatives to support sustainable active living.